2016
DOI: 10.17576/mjas-2016-2001-04
|View full text |Cite
|
Sign up to set email alerts
|

SPECTROSCOPIC ANALYSIS OF RHAMNOLIPID PRODUCED BY PRODUCED BY Pseudomonas aeruginosa UKMP14T

Abstract: Biosurfactant produced by Pseudomonas aeruginosa UKMP14T was optimized by growing the isolate in mineral salt medium (MSM) supplemented with 1% (v/v) glycerol and 1.3 g/L ammonium sulphate with C/N ratio of 14:1. The culture medium was incubated at 37°C, with an agitation speed of 150 rpm for 7 days. P. aeruginosa UKMP14T produced biosurfactant at 0.8 g/L after 7 days incubation. Anthrone assay proved biosurfactant was glycolipid. The biosurfactant was characterized by scanning electron microscope-energy dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
4
7
1
Order By: Relevance
“…The presence of a hydrophobic carbon source (chicken fats) favored the dominance of Rha(s)1 over Rha(s)2 as revealed by ESI-MS analysis shown in Section 2.2.1. Our results match those previously reported [42,48,49] where Rha(s)1 were the dominant compounds produced when the bacteria were grown in a medium supplemented with hydrophobic carbon sources, whereas using hydrophilic carbon sources favored the dominance of Rha(s)2.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of a hydrophobic carbon source (chicken fats) favored the dominance of Rha(s)1 over Rha(s)2 as revealed by ESI-MS analysis shown in Section 2.2.1. Our results match those previously reported [42,48,49] where Rha(s)1 were the dominant compounds produced when the bacteria were grown in a medium supplemented with hydrophobic carbon sources, whereas using hydrophilic carbon sources favored the dominance of Rha(s)2.…”
Section: Discussionsupporting
confidence: 92%
“…LC-MS analysis in the present study revealed the abundance of six compositionally different homologues of mono-rhamnolipid congeners. However, a di-rhamnose congener, i.e., Rha-Rha-C 8 -C 10 or Rha-Rha-C 10 -C 8 was also obtained at m / z 621.5 with a retention time of 12.49 min ( Figure 2 b), which was also evident in the study by Sabturani et al [ 69 ]. Rhamnolipids are predominantly produced by Pseudomonas sp.…”
Section: Resultssupporting
confidence: 79%
“…The transfer process of product for storage and further use from the Schott bottle (used for precipitating the rhamnolipid) was a difficult task as the product was in the form of a sticky paste, which led to loss of product. The yield obtained in present study using this method is way higher than the yield obtained by Sabturani et al (2016) using solvent extraction in combination with acid precipitation (dual recovery method). Table 2 summarises a comparison between these recovery methods and in view of the results obtained in our study.…”
Section: Biosurfactant Recoverycontrasting
confidence: 53%